Dr. Mohammed Asaduzzaman on agriculture and climate change in Bangladesh - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Climate change has become a major component of government plans for dealing with food security as nations see unprecedented changes in growing conditions. How are climate change concerns influencing agriculture policies in Bangladesh? Find out more at https://ccafs.cgiar.org/commission